A technical framework for costing health workforce retention schemes in remote and rural areas - Stormont Laura; Juquois Maud; Lemière Christophe; Vujicic Marko; Zurn Pascal; Campbell Jim; Rutten Martine; Braichet Jean-Marc (BMC, 2011)
Abstract Background Increasing the availability of health workers in remote and rural areas through improved health workforce recruitment and retention is crucial to population health. However, information about the costs of such policy interventions often appears incomplete, fragmented or missing, despite its importance for the sound selection, planning, implementation and evaluation of these policies. This lack of a systematic approach to costing poses a serious challenge for strong health policy decisions. Methods This paper proposes a framework for carrying out a costing analysis of interventions to increase the availability of health workers in rural and remote areas with the aim to help policy decision makers. It also underlines the importance of identifying key sources of financing and of assessing financial sustainability. The paper reviews the evidence on costing interventions to improve health workforce recruitment and retention in remote and rural areas, provides guidance to undertake a costing evaluation of such interventions and investigates the role and importance of costing to inform the broader assessment of how to improve health workforce planning and management. Results We show that while the debate on the effectiveness of policies and strategies to improve health workforce retention is gaining impetus and attention, there is still a significant lack of knowledge and evidence about the associated costs. To address the concerns stemming from this situation, key elements of a framework to undertake a cost analysis are proposed and discussed. Conclusions These key elements should help policy makers gain insight into the costs of policy interventions, to clearly identify and understand their financing sources and mechanisms, and to ensure their sustainability.